Relationship between prior inhaled corticosteroid use and benefits ofbudesonide/glycopyrronium/formoterol fumarate dihydrate on exacerbations, symptoms, health-related quality of life, and lung function in patients with chronic obstructive pulmonary disease: Analyses from the ETHOS study. (June 2022) - Singh, Dave; Rabe, Klaus F.; Martinez, Fernando J.; Krüll, Matthias; Jenkins, Martin; Patel, Mehul; Dorinsky, Paul
Abstract: Background: In the Phase III ETHOS study (NCT02465567), budesonide/glycopyrronium/formoterol fumarate dihydrate (BGF) triple therapy at two inhaled corticosteroid (ICS) doses reduced moderate/severe exacerbation rates and improved symptoms, health-related quality of life (HRQoL), and lung function versus glycopyrronium/formoterol fumarate dihydrate (GFF) or budesonide/formoterol fumarate dihydrate (BFF) dual therapy in patients with moderate-to-very-severe chronic obstructive pulmonary disease (COPD). Here, we assessed whether the benefit for BGF versus GFF was driven by patients who received ICS before randomization to GFF. Methods: ETHOS was a 52-week, randomized, double-blind, multicenter, parallel-group study in symptomatic patients with COPD and ≥1 moderate/severe exacerbation in the previous year. Patients received BGF 320/14.4/10 μg, BGF 160/14.4/10 μg, GFF 14.4/10 μg, or BFF 320/10 μg twice daily via a single metered dose Aerosphere™ inhaler. In these subgroup analyses, efficacy and safety were assessed in patients with or without prior ICS use in the 30 days before screening. Results: The modified intent-to-treat population comprised 8509 patients (prior ICS use, n = 6810 [80%]; no prior ICS use, n = 1699 [20%]). Moderate/severe exacerbation rates were reduced by 24% and 23% in patients with and without prior ICS use, respectively, with BGF 320 versus GFF. Benefits of BGF 320 versus GFF were also similar in patients with and without prior ICS use across other endpoints relating to exacerbations, symptoms, HRQoL, lung function, and safety. Trends were similar for BGF 160 versus GFF. Conclusion: Benefits on exacerbations, symptoms, HRQoL, and lung function with BGF versus GFF were observed, irrespective of prior ICS use in the 30 days before screening. Highlights: BGF 320 demonstrated benefits versus dual therapy, irrespective of prior ICS use. The BGF 320 safety profile was similar in patients with and without prior ICS use. Similar trends were observed for BGF 160.